Determinan Kesejahteraan Masyarakat Kabupaten/Kota Di Provinsi Bali - Maretania, Yolanda; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
The motive of this look at is to research the have an effect on of district minimal wages, funding, and family intake, each concurrently and in part, at the welfare of district/metropolis groups withinside the Province of Bali. The studies places have been performed in regencies/towns in Bali Province the use of secondary records that have been posted via way of means of the Bali Province Central Statistics Agency (BPS), and the Directorate General of Fiscal Balance (DJPK). The range of observations on this look at have been seventy two observations with eight years of time collection records from 2015-2022 and go segment records of nine regencies/towns in Bali Province. The records series technique on this look at changed into thru non-player remark techniques. The records used is a aggregate of time collection records and go segment records withinside the shape of panel records. The evaluation method used is descriptive evaluation and panel records regression.The panel records regression check consequences display that the maximum suitable version selected is the constant impact version (FEM). The consequences of the look at observed that district minimal wages, funding, and family intake concurrently have a great impact on people's welfare. District minimal wages have a fantastic and great impact, even as funding and family intake have a fantastic however in part insignificant impact at the welfare of district/metropolis groups withinside the Province of Bali. keyword : community welfare, district minimum wage, investment, household consumption.